Understanding culture shock and its relationship to intercultural communicative competence - Aulia, Muhammad; Fitrisia, Dohra; Haqqu, Rizki Maulidza (Universitas Syiah Kuala, 2023)
Culture shock has gained attention and been observed from multi-disciplinary perspectives in international education, such as from anthropology, psychology, cultural psychology, intercultural communication studies, linguistics, and many others. By synthesising the ABCs theory and intercultural communicative competence with their savoirs, the present study offers a perspective to analyse three international students culture shock experiences. As an explorative case study, the data were collected through in-depth interviews to extract the sojourners narratives, which were then transcribed in the form of text or quotations. It was found that the affective, behavioural, and cognitive dimensions were identified and emerged in each respondent. In the affective, overwhelming emotions, language limitation, and feelings of isolation were felt in various intensities. From the data, the respondents claimed to have lacked intrapersonal skills to prepare themselves for the culture of the host country along with the socio-cultural aspects. In addition, they found social support by individuals or officials essential for reducing negative feelings. In the behavioural dimension, these respondents started to adapt to the situation though they still found it challenging to confirm and clarify any unfamiliar encounters. Finally, in the cognitive dimension, the respondents mingled and integrated into the locals, both in their academic and social lives. It is suggested that elements of intercultural communicative competence, namely intercultural attitude, knowledge of the host culture, skills of relating and discovery, and critical cultural awareness may have the potential to manage culture shock effectively. It should be incorporated into international higher education and EFL pedagogy.